MINAT MAHASISWA AKUNTANSI STIE AMM MATARAM BERPROFESI DI BIDANG PERPAJAKAN - Sofiati Wardah; Baiq Saufil Wida Mulyati; Shinta Eka Kartika (Jurnal Aplikasi Akuntansi, 2020)
The gap between the number of tax experts such as DJP employees and tax consultants with the number of registered taxpayers is the duty of universities to print tax experts as one of the pillars in tax reform. The purpose of this study is to examine the effect of perceptions about taxation and perceptions about brevet taxation on interest in the taxation profession. The population in this study were accounting students at STIE AMM Mataram, with the sampling technique using stratified random sampling. The number of samples is 198 and data analysis is done by multiple linear regression. The results of the study show that perceptions of tax affect the interest in working in the taxation field. This can occur because career opportunities in the field of taxation are wide open and the role of taxes that are very important in development requires professional workers to be able to optimize state revenues and increase tax morale and tax compliance. Perception about brevet tax influences interest in profession in taxation. This can occur because brevet tax is one step that can be taken to equip themselves to enter the workforce in the field of taxation, thus increasing self-confidence in mastering the latest taxation material and expertise in the field of taxation marked by a certificate of brevet taxation.